Turbo-taxonomy: 21 new species of Myzostomida (Annelida) - Summers, Mindi M.; Al-Hakim, Iin Inayat; Rouse, Greg W. (Zootaxa, 2014)
An efficient protocol to identify and describe species of Myzostomida is outlined and demonstrated. This taxonomic approach relies on careful identification (facilitated by an included comprehensive table of available names with relevant geographical and host information) and concise descriptions combined with DNA sequencing, live photography, and accurate host identification. Twenty-one new species are described following these guidelines: Asteromyzostomum grygieri n. sp., Endomyzostoma scotia n. sp., Endomyzostoma neridae n. sp., Mesomyzostoma lanterbecqae n. sp., Hypomyzostoma jasoni n. sp., Hypomyzostoma jonathoni n. sp., Myzostoma debiae n. sp., Myzostoma eeckhauti n. sp., Myzostoma hollandi n. sp., Myzostoma indocuniculus n. sp., Myzostoma josefinae n. sp., Myzostoma kymae n. sp., Myzostoma laurenae n. sp., Myzostoma miki n. sp., Myzostoma pipkini n. sp., Myzostoma susanae n. sp., Myzostoma tertiusi n. sp., Protomyzostomum lingua n. sp., Protomyzostomum roseus n. sp., Pulvinomyzostomum inaki n. sp., and Pulvinomyzostomum messingi n. sp..